Zhiheshouwu ethanol extract induces intrinsic apoptosis and reduces unsaturated fatty acids via SREBP1 pathway in hepatocellular carcinoma cells. (September 2018) - Li, Hongliang; Xiang, Longchao; Yang, Nian; Cao, Fengjun; Li, Chen; Chen, Ping; Ruan, Xuzhi; Feng, Yibin; Zhou, Nian; Wang, Xuanbin
Abstract: Hepatocellular carcinoma (HCC) is the major incidence and one of the most life-threatening cancer. How to conquer HCC is a worldwide issue for patients. Zhiheshouwu ( Polygoni multiflori Radix Praeparata) is a Chinese medicinal herb exhibiting both lowering lipid and inhibiting cancer cells. However, it remains a matter if its inhibiting cancer cells is related to its lowering lipid. In this study, we investigate the effects of Zhiheshouwu ethanolic extract (HSWE) on apoptosis and the underlying mechanisms in Bel-7402 cells. The results showed that HSWE inhibited the proliferation with an increased level of ALT and AST in Bel-7402 cells. The decreased mitochondrial membrane potential (ΔΨm) was observed in HSWE-treated Bel-7402 cells. The flow cytometry results showed that HSWE triggered apoptosis. Since mitochondrial injury is characterized as intrinsic apoptotic cell death, these data indicated that HSWE may induce intrinsic apoptosis in Bel-7402 cells. In addition, HSWE decreased the production of unsaturated fatty acids, and inhibited the mRNA and protein of SCD1 and its up-stream factor, sterol-regulatory element binding proteins 1 (SREBP1), a master transcriptional regulator of lipogenic gene. Taken together, these data suggest that HSWE induces an intrinsic apoptosis, and reduced unsaturated fatty acids by blocking SREBP1 in hepatocellular carcinoma cells. Graphical abstract: